The effect of childhood brain tumours on the child and family: a prospective multidisciplinary follow up of children with intracranial tumours. - Penn, Anthony (My University, 2014)
Brain tumours are the second most common malignancy in childhood and account for approximately 20% of all childhood cancers. Children diagnosed with a primary brain tumour are at risk of significant morbidity. Measurement of quality of life (QOL) and health status (HS) are important in quantifying morbidity and identifying strategies to provide relevant support for patients. We aimed to: (1) Measure QOL and HS, using the PedsQL and HUI3 in children with brain tumours one, six and twelve months after diagnosis. (2) Compare QOL and HS with “normal” matched controls, and assess the relationship between parent- and self-report QOL and HS. (3) Identify determinants of overall QOL one year after diagnosis. A total of 45 patients and 43 controls were recruited to the study, with 37 patients and 42 controls and 27 patients and 31 controls eligible for comparison of QOL using parent-report and self-report PedsQL respectively. Thirty-five patients were eligible for analysis of determinants of parent-report and 26 for self-report QOL one year after diagnosis. There were 29 patients and 29 controls, and 21 patients and 22 controls eligible for comparison of HS between patients and controls using the parent-report and selfreport HUI3 respectively, one year after diagnosis. In addition, 29 and 21 patients were eligible for analysis of determinants of parent- and self-reported HS one year after diagnosis. Children with a primary brain tumour have significantly lower QOL/ HS in the first year after diagnosis than normal controls. QOL/ HS improved significantly over time, most notably in the six months after diagnosis. For patients, agreement between parent- and self-report was variable, with greater agreement for the more observable (physical), compared with less observable (psychosocial) domains. Agreement between parent- and self-report was better using the HUI3 than the PedsQL. Parents of patients rated their children's HRQL lower than their child did, while for controls this was reversed. Selective attention one month after diagnosis and infratentorial tumour site are most important in predicting both parent- and self-report overall QOL at 1 year after diagnosis. Larger multi-centre, prospective studies are needed to confirm these findings. Cognitive remediation and/ or pharmacological intervention, particularly aimed at children with infratentorial tumours may improve attention and subsequently QOL, and both merit further investigation. THE CLIC SARGENT BRAIN TUMOUR STUDY The study on QOL and its determinants as reported in this thesis was undertaken as part of a prospective longitudinal multidisciplinary study led by Dr Peta Sharples (Consultant Paediatric Neurologist) and Dr Stephen Lowis (Consultant Paediatric Oncologist), with support from Dr Renee McCarter (Consultant Neuropsychologist), Professor Mike Stevens (Professor of Paediatric Oncology), Dr Andrew Curran (Senior Registrar in Paediatric Neurology), Dr Linda Hunt (Senior Lecturer in Medical Statistics) and Mr Robert Shortman (Assistant Psychologist). The overall aim of the study was to investigate, in detail, the effects of childhood brain tumour on the child and family. More specifically, it was intended to investigate the effect of primary brain tumours on cognitive, neurological, behavioural and functional outcome by comparing children presenting with CNS tumours with matched normal controls. In addition, the study sought to assess the effect of the diagnosis and treatment on the primary carer’s emotional status, family functioning and other family variables. Assessments were to be undertaken at an early stage (within 1 month of diagnosis) and at 6 and 12 months thereafter with the intention that the findings would define the early rehabilitation needs and rate of recovery of this patient population. In collaboration with supervisors, particularly Dr. Sharples, the author of this thesis, after reviewing the literature on QOS in children diagnosed and treated for a primary intracranial tumour made the decision to use QOL as the primary outcome measure and dependent variable. During the study, the importance of assessment of the relationship between parent- and child-reported QOL using both the PedsQL and HUI3 became clear, and self- report HUI3, in addition to the PedsQL, was incorporated into the study and became an important theme of two of the papers submitted in support of the author’s thesis and the thesis itself. In addition to the contribution to the direction of the study, as mentioned above, the PhD applicant’s role in the study were (1) to recruit all patients and controls; (2) to collect, score and enter data relating to quality of life, behavioural/emotional functioning, neurological and physical outcome and family structure and function in patients, controls and their families; (3) to undertake preliminary data analysis for presentation at local, national and international meetings, and publication of results in the form of the four papers submitted in support of the PhD, Integrated Format; (4) to collate the data and divide it for publication in its current form; (5) to write and act as corresponding author for the four papers submitted in support of the PhD. Details of collection, handling and statistical analysis of data are covered below. For the purpose of this manuscript, only data used in the papers submitted in support of the author’s PhD are referred to, not other data arising from study.
Keywords: Brain Neoplasms--child; Family Relations